(untitled) (Homoeopathy for All, 2023)
Irritable bowel syndrome (IBS) is a chronic and debilitating functional gastrointestinal disorder that affects 9%-23% of the population across the world. IBS is a disorder of the movement of the intestines, the sensitivity of the nerves of the intestines, or how the brain controls some of these functions. It was p r e v i o u s l y k n o w n a s a gastrointestinal disorder. In this disability, and economic non-productivity. As the pathophysiology of IBS is poorly understood, the management generally focuses on the amelioration of symptoms and improvement in the quality of life. At present, the drugs available for the treatment of IBS have only a modest effect on symptom improvement and may not alter the natural history of the condition.